2018
DOI: 10.3762/bjnano.9.281
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-assisted fabrication of chalcopyrite micro-concentrator photovoltaics

Abstract: Micro-concentrator solar cells offer an attractive way to further enhance the efficiency of planar-cell technologies while saving absorber material. Here, two laser-based bottom-up processes for the fabrication of regular arrays of CuInSe2 and Cu(In,Ga)Se2 microabsorber islands are presented, namely one approach based on nucleation and one based on laser-induced forward transfer. Additionally, a procedure for processing these microabsorbers to functioning micro solar cells connected in parallel is demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…For the intensity range explored, V oc continuously increases, with a slightly reduced slope at higher illumination intensities, similar to the observations by Paire et al 19 for co-evaporated CIGSe micro-cells. On the other hand, Heidmann et al 45 and Ringleb et al 46 reported a decrease of V oc at around 30-40 suns for CISe micro-solar cells prepared via bottom-up laser nucleation and LIFT techniques. In our case, an average rate of increase of around 127 and 150 mV dec −1 for S500 and S1500, respectively, is determined.…”
Section: Device Light Concentration Seriesmentioning
confidence: 99%
“…For the intensity range explored, V oc continuously increases, with a slightly reduced slope at higher illumination intensities, similar to the observations by Paire et al 19 for co-evaporated CIGSe micro-cells. On the other hand, Heidmann et al 45 and Ringleb et al 46 reported a decrease of V oc at around 30-40 suns for CISe micro-solar cells prepared via bottom-up laser nucleation and LIFT techniques. In our case, an average rate of increase of around 127 and 150 mV dec −1 for S500 and S1500, respectively, is determined.…”
Section: Device Light Concentration Seriesmentioning
confidence: 99%
“…Another method for the fabrication of micro-CIGSe absorbers was presented by Ringleb et al [51]. Their approach uses LIFT, which consists of the transfer of a part of a donor film onto an acceptor substrate [52].…”
Section: Bottom-up Approachesmentioning
confidence: 99%
“…The main advantage of this method is the simplification of the whole fabrication process by reducing the number of steps in the micro-concentrator solar cell fabrication. The LIFT method was successfully implemented by Ringleb et al for CIGSe cells, transferring a metal precursor stack of Cu-In-Ga with thickness up to 1010 nm onto an acceptor Mo-coated glass substrate in a single transfer step, as shown in the optical micrograph image in figure 6(d) [51]. Subsequently, a standard selenization process in Se ambient, as well as an etching process by KCN to remove unwanted Cu-Se phases were performed.…”
Section: Bottom-up Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in thin film applications these phenomena are rarely attributed to the dewetting process, since the name of the resulting structures are nanoparticles or clusters but rarely droplets. Nevertheless, the origin of these structures from fluid-like states offers the opportunity for novel bottom-up techniques to produce precursor materials for functional materials, such as chalcopyrites [ 11 ], or precursors for complex structures, such as nanowires [ 12 ]. Silicon, germanium and silicon oxide nanowires, for example, can be formed on different substrates by using metal catalysts in the form of tin, indium or gold nanodroplets [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%